1996
DOI: 10.3354/meps145123
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fluxes in coral reefs. II. Eulerian study of inorganic carbon dynamics and measurement of air-sea CO2 exchanges

Abstract: Air-sea CO, exchanges and the part~al pressure of CO, were measured in surface water overlying 2 coral reefs: Moorea (French Polynesia, austl-a1 lvlnter, August 1992). where coral di\,ers~ty and surface cover are low, and Yonge Reef (Great Barr~er Reef, a~istral summer, December 1993), where coral diversity and cover are comparatively h~g h e r A procedure is proposed to estimate the potential CO2 exchange with the atmosphere by t a k~n g ~n t o account both the saturation level of oceanlc seawater and the equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
103
3
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 21 publications
(24 reference statements)
9
103
3
2
Order By: Relevance
“…NEP mainly alters DIC, with net organic carbon production (NEP > 0) reducing DIC concentrations as CO 2 is used and increasing pH and Ω aragonite . Air-sea CO 2 gas exchange affects DIC only, but typically exerts minor influence on DIC relative to NEC and NEP in reef environments with residence times of a few days, such as Bermuda (17,18). Consequently, comparison of salinity normalized changes in seawater DIC and TA (nDIC and nTA) between the reef and offshore can be used to evaluate the relative contribution and variability in reef NEC and NEP over time and space.…”
Section: Significancementioning
confidence: 99%
“…NEP mainly alters DIC, with net organic carbon production (NEP > 0) reducing DIC concentrations as CO 2 is used and increasing pH and Ω aragonite . Air-sea CO 2 gas exchange affects DIC only, but typically exerts minor influence on DIC relative to NEC and NEP in reef environments with residence times of a few days, such as Bermuda (17,18). Consequently, comparison of salinity normalized changes in seawater DIC and TA (nDIC and nTA) between the reef and offshore can be used to evaluate the relative contribution and variability in reef NEC and NEP over time and space.…”
Section: Significancementioning
confidence: 99%
“…Air-sea CO 2 flux values may be used to differentiate coral reefs that act as either sinks or sources of atmospheric CO 2 [6][7][8][9][10][11][12][13][14][15][16][17][18]. Positive values typically characterize coral reefs as a source of atmospheric CO 2 , whilst negative values may [20].…”
Section: Coral Reefs Of the Scs Act As Sources Of Atmospheric Comentioning
confidence: 99%
“…In recent years, several studies have examined the role of coral reefs and their contribution to atmospheric CO 2 by measuring seawater pCO 2 and atmospheric pCO 2 in coral reefs [6][7][8][9][10][11]. They indicate that although coral reefs are mostly net sources [7][8][9][10][11][12][13][14][15][16] of atmospheric CO 2 , they may also act as sinks [6,17,18] for atmospheric CO 2 . Suzuki et al [6] suggested that the contribution of coral reefs to atmospheric CO 2 is largely dependent on their topographic and oceanographic settings.…”
mentioning
confidence: 99%
“…However, both Eulerian (Atkinson and Bilger 1992; Gattuso et al 1993Gattuso et al , 1996 and Lagrangian (Barnes and Lazar 1993;Frankignoulle et al 1996) studies rely heavily on the assumption that the water column above the benthic community is fully mixed. Often in waters deeper than 3 m, the water column is sheared, so fluxes estimated from gradual changes in concentration using integration over the full depth of the environment can be erroneous.…”
mentioning
confidence: 99%